Treatment plan optimisation for reirradiation. (May 2023) - Murray, Louise; Thompson, Christopher; Pagett, Christopher; Lilley, John; Al-Qaisieh, Bashar; Svensson, Stina; Eriksson, Kjell; Nix, Michael; Aldred, Michael; Aspin, Lynn; Gregory, Stephen; Appelt, Ane
Highlights: The STRIDeR (Support Tool for Re-Irradiation Decisions guided by Radiobiology) pathway uses background dose to guide radiobiologically meaningful, anatomically-appropriate re-irradiation treatment planning within a commercial treatment planning system. Uniquely, the pathway can optimise voxel-by-voxel in equivalent dose in 2 Gy fractions (EQD2) The EQD2 optimisation was used to produce re-irradiation treatment plans to illustrate the use of the STRIDeR pathway. A selective approach to deformable image registration was employed to take account of anatomical change between treatment courses. The development of scientifically-driven and standardised strategies such as the STRIDeR pathway, to improve and learn from re-irradiation, is essential to optimise the therapeutic ratio for future patients. Abstract: Background: The STRIDeR (Support Tool for Re-Irradiation Decisions guided by Radiobiology) project aims to create a clinically viable re-irradiation planning pathway within a commercial treatment planning system (TPS). Such a pathway should account for previously delivered dose, voxel-by-voxel, taking fractionation effects, tissue recovery and anatomical changes into account. This work presents the workflow and technical solutions in the STRIDeR pathway. Methods: The pathway was implemented in RayStation (version 9B DTK) to allow an original dose distribution to be used as background dose to guide optimisation of re-irradiation plans. Organ at risk (OAR) planning objectives in equivalent dose in 2 Gy fractions (EQD2) were applied cumulatively across the original and re-irradiation treatments, with optimisation of the re-irradiation plan performed voxel-by-voxel in EQD2. Different approaches to image registration were employed to account for anatomical change. Data from 21 patients who received pelvic Stereotactic Ablative Radiotherapy (SABR) re-irradiation were used to illustrate the use of the STRIDeR workflow. STRIDeR plans were compared to those produced using a standard manual method. Results: The STRIDeR pathway resulted in clinically acceptable plans in 20/21 cases. Compared to plans produced using the laborious manual method, less constraint relaxation was required or higher re-irradiation doses could be prescribed in 3/21. Conclusion: The STRIDeR pathway used background dose to guide radiobiologically meaningful, anatomically-appropriate re-irradiation treatment planning within a commercial TPS. This provides a standardised and transparent approach, offering more informed re-irradiation and improved cumulative OAR dose evaluation.